Análise comparativa entre os tempos gastos na apicetomia por ponta diamantada e pelos lasers CO2 e Er:YAG na apicectomia - Daniel Pozza (2005)
Objective: The aim of this research was to compare the time spent with the use of diamond tips and lasers of CO2 and Er:YAG in apicoectomies of extracted human teeth. Methodology: 36 human cuspid teeth were endodontically treated and randomly divided into three groups according to the cut instrument. The apicoectomy was performed at 90 degrees and 3mm from the extreme teeth apex. Results: Through an average analysis, the lowest time for apicoectomy happens in the diamond tip group. Statistical analyses showed differences (p<0.01) among bur and laser groups. Conclusion: Apart from statistical differences among groups these represents only a few seconds. It was concluded that the three methods allow the surgeon agility in the realization of the periapical surgical procedures.